A Dynamic Classification Approach for Nursing - Hardiker, Nicholas R. (American Medical Informatics Association, 2011)
Nursing has a long tradition of classification, stretching back at least 150 years. The introduction of computers into health care towards the end of the 20(th) Century helped to focus efforts, culminating in the development of a range of standardized classifications. Many of these classifications are still in use today and, while content is periodically updated, the underlying classification structures remain relatively static. In this paper an approach to classification that is relatively new to nursing is presented; an approach that uses formal Web Ontology Language definitions for classes, and computer-based reasoning on those classes, to determine automatically classification structures that more flexibly meet the needs of users. A new proposed classification structure for the International Classification for Nursing Practice is derived under the new approach to provide a new view on the next release of the classification and to contribute to broader quality improvement processes.